ANALYSIS OF COLLABORATION SKILLS DEVELOPMENT IN STUDENTS THROUGH PROBLEM SOLVING LEARNING MODEL - Sailendra, Dinda Pramestia; Taufik, M.; Pribadi, Reksa Adya (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2024)
In the era of globalization and the rapid development of technology, students should have more comprehensive and holistic skills to face future challenges. One of the most needed skills is collaboration skills. The path of education and learning is one of the provisions for developing these skills, including applying a problem-solving learning model. This research aims to determine learning planning with the problem-solving model, the process of implementing learning with the problem-solving model, and the results of developing collaboration skills in students through the problem-solving model. This research uses a qualitative descriptive method where the data collection uses data in the form of words and pictures. The resource persons of this research are 22 people consisting of 1 school principal, 2 2nd grade teachers, and 19 students of 2nd grade Andalusia Class. The research results showed that in the learning activities with the problem-solving model, the teacher goes according to the plans prepared in the lesson plan and carries out learning activities according to the problem-solving syntax to develop collaboration skills for students, especially in 2nd grade Andalusia class.